2001
DOI: 10.1038/35074122
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ and lymphocytes prevent primary tumour development and shape tumour immunogenicity

Abstract: Lymphocytes were originally thought to form the basis of a 'cancer immunosurveillance' process that protects immunocompetent hosts against primary tumour development, but this idea was largely abandoned when no differences in primary tumour development were found between athymic nude mice and syngeneic wild-type mice. However, subsequent observations that nude mice do not completely lack functional T cells and that two components of the immune system-IFNgamma and perforin-help to prevent tumour formation in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
1,620
7
37

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 2,454 publications
(1,734 citation statements)
references
References 18 publications
70
1,620
7
37
Order By: Relevance
“…These data are consistent with those reported for IFN-␥ production by homeostasis-induced memory CD8 T cells (8). IFN-␥ has not only been shown to correlate with antitumor effects of immunotherapies in vivo, but also to help prevent tumor formation in vivo (28). Although tumor lysate pulsing of the DC is required for optimal antitumor activity, in some instances we have observed that repetitive immunizations with unpulsed DC could induce a nonspecific response in the BMT setting but not in conventional, fully immunocompetent mice (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…These data are consistent with those reported for IFN-␥ production by homeostasis-induced memory CD8 T cells (8). IFN-␥ has not only been shown to correlate with antitumor effects of immunotherapies in vivo, but also to help prevent tumor formation in vivo (28). Although tumor lysate pulsing of the DC is required for optimal antitumor activity, in some instances we have observed that repetitive immunizations with unpulsed DC could induce a nonspecific response in the BMT setting but not in conventional, fully immunocompetent mice (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…The coexistence in cancer patients of tumor cells and tumorspecific circulating CD8ϩ T cells remains an intriguing paradox of tumor immunology (26,27). Our present results provide further evidence for the concept of immune selection in neoplastic development by showing that CTL selection pressure can lead to a striking adaptation of the tumor target, involving morphological change to escape immune surveillance.…”
Section: Discussionsupporting
confidence: 61%
“…4). Some MCA-induced sarcomas derived from RAGdeficient mice were previously reported to be unedited and rejected by a combination of CD8 ϩ and CD4 ϩ T cells in WT mice (27). MyD88 Ϫ/Ϫ mice were able to reject these highly immunogenic regressor MCA sarcomas (27) as efficiently as WT mice (Fig.…”
Section: Myd88 Deficiency Does Not Compromise Immune Rejection Of Tramentioning
confidence: 92%